Characterization of the main immunogenic proteins in Brucella infection for their application in diagnosis of brucellosis. (June 2020) - Tian, Mingxing; Song, Meiying; Yin, Yi; Lian, Zhengmin; Li, Zichen; Hu, Hai; Guan, Xiang; Cai, Yumei; Ding, Chan; Wang, Shaohui; Li, Tao; Qi, Jingjing; et al.
Highlights: Antibody production rule of immunogenic proteins was drawn in Brucella infection. The BP26 and BLS proteins were two best immunogenic proteins. It is unsuitable for BP26 and BLS as diagnostic antigens due to false-positive result. Abstract: Brucellosis is an important zoonotic bacterial disease widespread in the world. The key step of control this disease is accurate diagnosis and elimination of diseased animals. The classic diagnostic methods, such as tube agglutination test, are inaccurate and nonspecific, because of cross-reaction with Yersinia enterocolitica serotype O:9. Previously, several proteins were reported as Brucella main immunogens. In this study, we used animal infection model to evaluate antibody production against OMP16, BP26, BLS, BCSP31, VirB12, SodC and GroEL proteins and investigated their application in diagnosis of brucellosis. The results showed that the BP26 and BLS are two best immunogenic proteins. In further study, we detected 44 clinical bovine sera using western blot, showing that the BP26 and BLS reacted with 30 Brucella -positive sera, but false-positive results were also shown in 14 Brucella -free sera. In an indirect ELISA assay, compared to lipopolysaccharide-based ELISA, the conformance of the BP26-based ELISA was 92.68 % in Brucella -positive sera, but only 52.94 % in Brucella -free sera. The BLS-based ELISA can hardly differentiate positive sera from negative sera. Besides, truncated fragments of the BP26 protein cannot exclude false-positive results in detection of Brucella -free sera. Altogether, although Brucella main immunogenic proteins have good reaction with Brucella -positive sera, false-positive reaction with Brucella -free sera may lead to misdiagnosis of brucellosis, suggesting that it should be more careful to use these immunogenic proteins as antigen targets to diagnosis of brucellosis.